CATALYTIC OXIDATION OF FERROUS IRON TO INCREASE THE EFFICIENCY OF URANIUM LEACHING - A.Z. Abilmagzhanov; N.S. Ivanov; M.S. Malimbaev; I.Y. Adelbayev; A.E. Nurtazina; A.D. Altynbek; N.M. Shokobayev (Academic Scientific Journal of Chemistry, 2020)
Currently, enterprises of the metallurgical complex in Kazakhstan are faced with the problem of raw materials quality and the impossibility of productive processing of a number of ores. In recent years, not a single significant mineral deposit has been discovered, and previously discovered deposits are not of industrial interest, due to the low content of mineral components. «Kazatomprom» enterprises producing uranium by in-situ leaching method (ISL) were no exception. Today, the metal content in productive solutions is steadily decreasing; to increase the concentration of uranium production, it is necessary to increase the amount of reagent consumption, which leads to significant costs. The cost of uranium in the world market has decreased, significant production costs lead to a decrease in the profitability of production. The mechanism of uranium oxidation by iron ions is catalytic in nature. To regenerate iron, air oxygen was supplied to the leaching solution along with the oxidizing agent. The paper presents the results of studies on the possibility of intensifying ISL of uranium by introducing sodium nitrite into the leaching solution with additional supply of compressed air or oxygen to the leaching solution to ensure the catalytic oxidation of iron (II) ions by dissolved oxygen. The positive effect of stirring is proven. Research works at the testing ground with simultaneous supply of sodium nitrite and pure oxygen to LS allowed reaching 1.0 and 1.2 g/l Fe (III) concentrations